Optimal Timing of Delivery in Small for Gestational Age Fetuses Near Term: A National Cohort Study - Kazemier, B. M.; Voskamp, B. J.; Ravelli, A. C. J.; Pajkrt, E.; Groot, C. J. M. de; Mol, B. W. J. (American Journal of Perinatology, 2015)
Objective Our aim was to study the competing risks of antepartum versus intrapartum/neonatal death in small for gestational age (SGA) and non-SGA fetuses.Study Design We performed a national cohort study using all singletons delivered between 36 and 426/7 weeks without hypertension, preeclampsia, diabetes, congenital anomalies, or noncephalic presentation from the Netherlands Perinatal Registry (1999–2007). The resultant cohort was divided in three groups based on birth weight by gestational age (SGA < P5 group, 61,021 deliveries; SGA P5–10 group, 58,902 deliveries; non-SGA group 1,168,523 deliveries). We compared the mortality risk of delivery with expectant management.Results Delivery was associated with more mortality than expectant management for 1 week from 39 weeks onward in the non-SGA group (relative risk [RR], 1.26; 95% confidence interval [CI], 1.05–1.50). For the SGA < P5, expectant management for 1 more week was associated with more mortality from 38 weeks onward although this only reached statistical significance from 40 weeks onward (RR, 2.46; 95% CI, 1.80–3.36).Conclusion At 36 and 37 weeks, delivery is associated with a higher risk of mortality in SGA < P5 fetuses than expectant management. Delivery of SGA < P5 fetuses at 38 and 39 weeks is associated with the best perinatal outcome whereas for non-SGA fetuses this is at 39 to 40 weeks.
Keywords: small for gestational age; optimal timing delivery; antepartum death; neonatal death